2012
DOI: 10.2147/ijn.s29788
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy for glioma using cyclic RGD-entrapped polyionic complex nanomicelles

Abstract: Background:The purpose of this study was to test the efficacy of cyclic Arg-Gly-Asp (RGD) peptide conjugated with polyionic complex nanomicelles as targeted therapy for glioma. Methods: A stable cyclic RGD polyionic complex nanostructure, ie, a c(RGDfC) polyionic complex micelle, was synthesized and its biocompatibility with cultured neurons was assessed using a cell viability assay. Targeted binding to cultured glioma cells was evaluated by the CdTe quantum dot marking technique and a cell viability assay. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…RGD (R, arginine; G, glycine; D, aspartic acid) is a specific ligand for integrin receptors. , The expression levels of integrin receptors are greatly improved in cerebral ischemia, making it easier for nanocarriers containing RGD to enter vascular endothelial cells of the infarcted area by binding to the overexpressed integrins . Therefore, gene carriers conjugated with RGD peptides have recently gained attention as a potential and efficient approach for treating ischemic diseases. , Moreover, many studies have used RGD-modified nanoparticles for the treatment of neurological diseases, and Zhang, L. et al demonstrated that RGD-modified synthetic hyperbranched cationic polymers can cross the blood–brain barrier in vivo. Consequently, in this study, we selected RGD as a targeting ligand and used it for the targeted therapy of ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…RGD (R, arginine; G, glycine; D, aspartic acid) is a specific ligand for integrin receptors. , The expression levels of integrin receptors are greatly improved in cerebral ischemia, making it easier for nanocarriers containing RGD to enter vascular endothelial cells of the infarcted area by binding to the overexpressed integrins . Therefore, gene carriers conjugated with RGD peptides have recently gained attention as a potential and efficient approach for treating ischemic diseases. , Moreover, many studies have used RGD-modified nanoparticles for the treatment of neurological diseases, and Zhang, L. et al demonstrated that RGD-modified synthetic hyperbranched cationic polymers can cross the blood–brain barrier in vivo. Consequently, in this study, we selected RGD as a targeting ligand and used it for the targeted therapy of ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…cRGD was also exploited by Liu et al to target glioma cells [ 121 ]. They formulated homogeneous polyionic micelles based on maleimide-PEG-g- N -diethanolamine (PDEA) and maleimide-PEG-g-poly(aspartamide) (PAsp), with an average diameter of 60 nm.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…Integrin plays a critical part in the regulation of the growth, metastasis, and angiogenesis of tumors. [30][31][32] Therefore, creation of RGD-conjugated quantum dots (QDs-RGD) can help to trace and image tumor cells in vivo.…”
Section: Et Almentioning
confidence: 99%